Self tuning digital proportional integral derivative (PID) controller applied to flow and level processes - Genota, Ma. Lyn N. (Animo Repository, 1993)
A proportional-plus-integral-plus-derivative (PID) controller, or a three-mode control is the most sophisticated, continuous controller available in feedback loops. It gives rapid response and it exhibits no offsets. With the progress of computer technology, new control methods are being developed. Rapid progress has been made in adaptive control theory and various applications for practical use including process control. An intelligent PID controller is a self-tuning controller. These controllers exist for the control of difficult processes. The self-tuning PID controller is able to estimate the optimum value of PID parameters according to process behavior that change under a closed loop control condition and to tune PID parameters until a good control criteria is achieved. This is an interesting control option wherein, by using the Ziegler Nichols Procedures, the determination of the optimal proportional, integral and derivative control constants is already possible. During the self-tune sequence, the controller introduces a number of step changes within the tolerances allowed by the operator in order to characterize the system response. The value of P, Ti and Td are evaluated and changed if the criteria has not yet been achieved. The first part of this research covers the interfacing of the processes to the computer which will act as the self tuning PID controller and data recorder. The second part is the development of PID self-tuning Controller software applied to the level and flow processes available at the Process Control Laboratory of the College of Engineering, De La Salle University.